Environmental aspects of baby food production - Cherevychna , N. I.; Kramarenko , D. P.; Hirenko , N. I. (Man and Environment. Issues of Neoecology, 2026)
Purpose. To study the current state of the baby food market in Ukraine in terms of environmental aspects of production, quality and safety management of raw materials and finished products, environmental labelling and harmonisation of national legislation in the field of baby food with European standards.Methods. System-structural, abstract-logical, statistical method, methods of induction, deduction, comparison, as well as system-analytical method.Results. The article presents the national (commodity and medical) and European classification of baby food. It is determined that 64 % of the Ukrainian market is made up of imported products (mainly Nestlé, Danone, HiPP brands), which have advantages due to the use of specialised European raw material zones. The article describes domestic baby food producers that compete with imported analogues. It is noted that some of them are introducing environmental innovations in production and packaging. The author highlights the impact of the latest legislative changes of 2025-2026 on environmental labelling, safety control and environmental friendliness of baby food products. This indicates a significant shift in the vector of greening at the legislative level towards the harmonisation of Ukrainian legislation with European legislation. The article also examines the problem of greenwashing in Ukraine and the effectiveness of the national legislative framework in combating the misuse of pseudo-environmental labelling.Conclusions. The article confirms that the introduction of an environmental labelling system is a key preventive mechanism for ensuring the safety of baby food. Global and Ukrainian sociological studies show a high demand for organic baby food. However, the spread of greenwashing reduces the trust of Ukrainian consumers in local brands in favour of European ones. Overcoming this problem and focusing on the concept of Zero Waste and sustainable development are critical to increasing the competitiveness of domestic producers.